Sexual Violence, Consent, and Contradictions: A Call for Communication Scholars to Impact Sexual Violence Prevention - Katie D Scott; Clint Graves (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
The goal of this paper is to provide an overview of the conflicting findings from existing sexual violence and consent communication research with the intention of motivating communication scholars to study these areas. Generally, normative roles and alcohol add to the inherent complexity of consent communication. Moreover, contradictory findings in the literature make it difficult to define a practicable approach to the reduction of sexual violence across college campuses. This paper broadly reviews the current literature in this area of research with the ultimate goal of creating a guiding research agenda based in communication theory. Sexual violence prevention programming may benefit from this insight gleaned from communication research. For future research, we suggest consent communication, sexual negotiation, and other factors influencing sexual violence as topics that may inform more specifically targeted prevention programming, leading to measurable reduction in the instances of sexual violence.
Keywords: consent communication; sexual violence prevention; sexual behavior